2005
DOI: 10.1038/sj.npp.1300911
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Drugs Inhibit the Human Corticotropin-Releasing-Hormone Gene Promoter Activity in Neuro-2A Cells—an Involvement of Protein Kinases

Abstract: Antipsychotic drugs can regulate transcription of some genes, including those involved in regulation of hypothalamic-pituitary-adrenal (HPA) axis, whose activity is frequently disturbed in schizophrenic patients. However, molecular mechanism of antipsychotic drug action on the corticotropin-releasing hormone (CRH) gene activity has not been investigated so far. This study was undertaken to examine the influence of conventional and atypical antipsychotic drugs on the CRH gene promoter activity in differentiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 60 publications
1
33
0
Order By: Relevance
“…Inhibition of HPA axis by neuroleptics may be mediated by their ability to inhibit CRH gene promoter activity. Clozapine and chlorpromazine modulate CRH activity mainly via activation of the PI3K/Akt pathway, but PKC-related pathway may be also involved (Basta-Kaim et al 2006). Interestingly, olanzapine increased calcitonin gene-related peptide (CGRP) immunoreactivity in the striatum, frontal cortex, and hypothalamus (Angelucci et al 2008), whereas the pronounced adrenocorticotropic hormone (ACTH) and cortisol lowering performed by atypical neuroleptics is possibly related to the downregulation of serotonergic, adrenergic, and histaminergic receptors (Cohrs et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of HPA axis by neuroleptics may be mediated by their ability to inhibit CRH gene promoter activity. Clozapine and chlorpromazine modulate CRH activity mainly via activation of the PI3K/Akt pathway, but PKC-related pathway may be also involved (Basta-Kaim et al 2006). Interestingly, olanzapine increased calcitonin gene-related peptide (CGRP) immunoreactivity in the striatum, frontal cortex, and hypothalamus (Angelucci et al 2008), whereas the pronounced adrenocorticotropic hormone (ACTH) and cortisol lowering performed by atypical neuroleptics is possibly related to the downregulation of serotonergic, adrenergic, and histaminergic receptors (Cohrs et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, even atypical antipsychotics, used for the treatment of acute mania, seem to modulate the PKC pathway. Clozapine for instance, decreased PKC activity after 5 days of exposure in mouse neuroblastoma cells [39].…”
Section: Mood Stabilizers and Antimanic Agentsmentioning
confidence: 96%
“…86 A similar analysis in mouse neuroblastoma cells demonstrated that 5 days of both clozapine and chlorpromazine increased phospho-Ser473-Akt without increasing total Akt levels. 87 Olanzapine has been similarly shown to increase levels of phosphoSer473-Akt in PC12 cells although total Akt remained the same. 88 This effect was dependent on PI3K, suggests an additional mechanism of antipsychotic effects on Akt and may be related to differences in cell line.…”
Section: Possible Mechanisms Of Antipsychotic-induced Disordered Glucmentioning
confidence: 96%
“…86 Similar results were observed in another study of mouse neuroblastoma cells exposed to 5 days of antipsychotic; active, nonphosphorylated GSK-3b decreased after exposure to both chlorpromazine and clozapine. 87 In mice that had been treated with clozapine for 68 days it was observed that although insulin receptor activity decreased and phospho-Ser21-GSK-3a and phospho-Ser9-GSK-3b remained the same, total GSK-3a and -b levels, and thus activity, were decreased. 74 Opposite effects were noted in glioblastoma cells in which clozapine had the effect of dephosphorylating GSK-3b at Ser9, 92 possibly related to differences in cell line.…”
Section: Possible Mechanisms Of Antipsychotic-induced Disordered Glucmentioning
confidence: 99%